2019
DOI: 10.21315/jcdc2019.24.2.7
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Competency Knowledge in Safety Training among Construction Personnel

Abstract: Competency in safety is important for construction personnel and it is compulsory for all construction personnel in Malaysia to attend safety training. A literature review of the recommended training module revealed gaps in evaluating the effectiveness of competency knowledge among 200 construction personnel. Therefore, this article investigates the level of competency knowledge among construction personnel towards construction accidents based on safety training in Malaysia's construction industry. A structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Safety management ability is an important quality of construction personnel. Although the acquisition ability of safety knowledge of construction personnel is not significantly related to age and experience, there are significant differences in safety management ability in professional classification (38). The latest research found that new construction equipment (such as GPS and physiological sensors) can improve the management level of occupational safety and health (39).…”
Section: Introductionmentioning
confidence: 99%
“…Safety management ability is an important quality of construction personnel. Although the acquisition ability of safety knowledge of construction personnel is not significantly related to age and experience, there are significant differences in safety management ability in professional classification (38). The latest research found that new construction equipment (such as GPS and physiological sensors) can improve the management level of occupational safety and health (39).…”
Section: Introductionmentioning
confidence: 99%